Obesity and brain function - Letra, Liliana; Seica, Raquel (Advances in neurobiology ;, 2017)
This compendium provides a wide view covering everything from molecular mechanisms and risk factors for neurological disorders to the effects of bariatric surgery on brain function and functional neuroimaging applied to obesity research. The impact of obesity on brain function and the development of neurodegenerative and neuroinflammatory disorders has been understudied, despite the recent proliferation of obesity research. Among the topics covered are adipose biology, the adipose tissue - gut - brain axis, brain energy metabolism, dementia, cerebrovascular disease, and multiple sclerosis.